2021
DOI: 10.1111/aor.14120
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracorporeal membrane oxygenation in adult liver transplant patients: A qualitative systematic review of literature

Abstract: BACKGROUNDThe critical shortage of donor organs for adult solid organ transplantation underscores the need to expand the donor pool. This expansion could include not only more aggressive organ donation from an enlarged pool of critically ill intensive care unit (ICU) patients but also more aggressive management of sick recipients in order to obtain the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Two additional systematic reviews have assessed liver transplantation from ECMO-supported donors, which importantly did not specifically denote whether ECMO cannulation was performed for donation or therapeutic intent and have also noted generally acceptable outcomes. The first, assessing 187 liver transplants, noted a 1-year patient survival of 89.8%, PNF incidence of 1.6%, and bile leak/stricture rate of 13.2%, 9 while the second, specifically examining DBD VA-ECMO-supported donors, identified 17 studies contributing 156 liver transplants, and noted a pooled PNF incidence of 1% and acceptable, similar 1-year graft survival in 16 of 17 investigations 16 . Our observed 87.1% 1-year graft survival with zero cases of PNF, therefore, appears largely concordant with the published literature, although, like many of the previously published studies, our data source limits our ability to make significant conclusions related to biliary complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two additional systematic reviews have assessed liver transplantation from ECMO-supported donors, which importantly did not specifically denote whether ECMO cannulation was performed for donation or therapeutic intent and have also noted generally acceptable outcomes. The first, assessing 187 liver transplants, noted a 1-year patient survival of 89.8%, PNF incidence of 1.6%, and bile leak/stricture rate of 13.2%, 9 while the second, specifically examining DBD VA-ECMO-supported donors, identified 17 studies contributing 156 liver transplants, and noted a pooled PNF incidence of 1% and acceptable, similar 1-year graft survival in 16 of 17 investigations 16 . Our observed 87.1% 1-year graft survival with zero cases of PNF, therefore, appears largely concordant with the published literature, although, like many of the previously published studies, our data source limits our ability to make significant conclusions related to biliary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the use of ECMO to improve donor utilization have largely focused on ECMO as a strategy to stabilize donors specifically for the purpose of organ donation 2–6 . The few studies assessing transplantation patterns and outcomes when using organs from ECMO-supported donors who were cannulated for non–organ donation purposes have shown reasonable outcomes to promote their use in select settings 7–10 . These studies, however, have been limited by small sample sizes, which limit the extent of their analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Reid et al performed a systematic review of literature published from January 1, 2000 to April 24, 2020 on adult LT recipients (pre- or post-transplant) who underwent ECMO. 68 Forty-one articles were identified that fit the criteria. Sixty-one recipients were placed on ECMO intraoperatively or postoperatively.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…However, there are limited data and sporadic case reports on the use of ECMO in kidney transplantation, both pre‐donation, and post‐transplantation 12 . Our group has performed systematic reviews of the use of ECMO in pediatric liver and kidney transplantation, as well as adult liver transplantation 13,14 . The purpose of this study was to perform a qualitative, systematic review and analyze all existing literature regarding outcomes, complications, and mortality for adult patients receiving veno‐venous (VV) or veno‐arterial (VA) ECMO support, either pre‐ or postrenal transplant.…”
Section: Introductionmentioning
confidence: 99%
“…12 Our group has performed systematic reviews of the use of ECMO in pediatric liver and kidney transplantation, as well as adult liver transplantation. 13,14 The purpose of this study was to perform a qualitative, systematic review and analyze all existing literature regarding outcomes, complications, and mortality for adult patients receiving veno-venous (VV) or veno-arterial (VA) ECMO support, either pre-or postrenal transplant. With this review, we aim to evaluate the impending role of ECMO in kidney transplant patients to inform practice guidelines.…”
mentioning
confidence: 99%